PENGARUH HARGA, KUALITAS PRODUK DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE (STUDI KASUS PADA MAHASISWA STIE MUHAMMADIYAH CILACAP) - Werdiasih, Rustina Dewi; Yauhana Flaurencya Devi (JURNAL EKONOMI, 2019)
This study aims to determine influence price, product quality and trust in online purchasing decisions on STIE Muhammadiyah Cilacap students. The method used in this study uses quantitative methods and the sample used in this study amounted to 54 student respondents in STIE Muhamadiyah Cilacap using purposive random sampling method. Methods of collecting data with a questionnaire. Data analysis used multiple regression analysis. The results showed that in the regression F test conducted it was found that all variables including price, product quality and trust simultaneously influence online purchasing decisions, this is indicated by the F test value which results in a calculated Fvalue of 9,150 greater than Ftabel 2,78. Based on the results of the T test which is carried out partially the variables that influence the product quality are online purchasing decisions. This is indicated by the value of T count 3,188 while the variable price of 1,427 and trust of 0,329 partially does not affect online purchasing decisions with a T table of 1,673. Keywords : Price, Product Quality, Trust, Purchasing decision